Spanish cross-cultural adaptation and validation of the Oslo Sports Trauma Research Centre (OSTRC) overuse injury questionnaire in handball players - Martínez-Cal, Jesús; Molina-Torres, Guadalupe; Carrasco-Vega, Elio; Barni, Luca; Ventura-Miranda, María Isabel; González-Sánchez, Manuel (MDPI, 2023)
Objectives: The aim of this study was the cultural adaptation, Spanish translation and validation of the Oslo Sports Trauma Research Centre (OSTRC) Overuse Injury Questionnaire in an adult population. Design: In this study, a cross-sectional design was used. Methods: This study was divided into two phases: (1) cross-cultural adaptation of the original version of the OSTRC to a Spanish version (OSTRC-Sp) and (2) analysis of the psychometric properties of the OSTRC-Sp. A total of 427 handball players of both sexes and over 18 years of age participated in the study. Results: The translated version of the questionnaire showed a very high internal consistency (Cronbach's α = 0.954), while the subscales showed an internal consistency between 0.832 and 0.961, with the endmost values being for shoulder and low back pain, respectively. On the other hand, when analysing item responses, the OSTRC-Sp showed ICC values ranging from 0.844 to 0.956, the former being for the first back question (back_1), and the latter for the fourth shoulder question (shoulder_4), in line with most published versions. Conclusion: The Spanish version of the OSTRC is a reliable and valid tool that can be used by researchers and clinicians in a Spanish-speaking population with musculoskeletal disorders.
Keywords: Lesiones y heridas; Balonmano; Cuestionario; OSTRC; Overuse injury; Cross-cultural adaptation; Validation; Questionnaire